HE EFFECT OF SITZ BATH THERAPY ON INTENSITY OF PERINEALWOUND PAIN IN POSTPARTUM MOTHER AT PMB DINCE SAFRINA OF PEKANBARU Reza Rantika : rezarantika59@gmail.com IN 2019 - Rantika, Reza; Susanti, Ari; ., Yanti (JURNAL IBU DAN ANAK, 2020)
Abstract Perineal wound pain is discomfort that occurs in postpartum mothers. Based onclinical practice experience in PMB Dince Safrina, 70% of postpartum motherscomplained of pain and feeling uncomfortable. One of the alternatives to reduceperineal wound pain is sitz bath therapy. This study was to determine the effectof sitz bath therapy on perineal wound pain in postpartum mothers. This quasyexperimental study used one group pre-test and posttest design. This researchwas conducted at PMB Dince Safrina in March-June 2019. The population wasall 6-hour postpartum mothers who had perineal wound at PMB Dince Safrinawith a sample size of 17 taken by purposive sampling technique. The method ofdata collection was observation with an observation sheet that contained a scaleof pain intensity measurement using the Numeric Rating Scale (NRS). The resultsshowed that the average intensity of perineal wound pain before and after sitzbath therapy was 5.59 (SD 0.939) and 2.47 (SD 0.943). The results ofstatistical tests using Wilcoxon on the 95% confidence level found that therewas an effect of sitz bath therapy on the intensity of perineal wound pain inpostpartum mothers (p value = 0.000). It is recommended for midwives toconsider sitz bath therapy as an alternative in the provision of nonpharmacological care to reduce the intensity of perineal wound pain inpostpartum mothers.